1986
DOI: 10.1007/bf00261466
|View full text |Cite
|
Sign up to set email alerts
|

Plantlet regeneration from glume calli of maize (Zea mays L.)

Abstract: Totipotent callus cultures were established from anther-free glumes of 'Sweet corn', 'Seed corn,' 'DHM 103' and 'DHM 101' on MS medium supplemented with 1-2 mg/l 2,4-D. The callusing response of the glumes was tested on six different media. Glumes at the uninucleate stage of pollen development callused with a high frequency compared to other stages. Organogenesis was observed in 40% of the cultures on media devoid of hormones. A total of 76 plantlets were regenerated on medium with 0.5-1.0 mg/l of both IAA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…The general view is that the younger the inflorescence and the less committed the primordia are to producing florets, the greater the number of shoots produced. On the contrary, many plantlets regenerated from well-developed inflorescences of grasses [13] taken when the tips of the flag leaves were just emerging, from 7-15 cm maize tassels [4], even from emerged orchard grass inflorescences [9] when pollen stages ranged from pre-meiotic to mature pollen grains. Our result that developmental stages do not critically affect callus and shoot formation in sorghum inflorescence culture is not in agreement with those reported by Brettell et al [14], who found that sorghum inflorescences less than 20mm in length produced more apparently embryo-like structures than the panicles over 20 mm in length.…”
Section: Response To In Vitro Culture Of Immature Inflorescences Frommentioning
confidence: 99%
See 1 more Smart Citation
“…The general view is that the younger the inflorescence and the less committed the primordia are to producing florets, the greater the number of shoots produced. On the contrary, many plantlets regenerated from well-developed inflorescences of grasses [13] taken when the tips of the flag leaves were just emerging, from 7-15 cm maize tassels [4], even from emerged orchard grass inflorescences [9] when pollen stages ranged from pre-meiotic to mature pollen grains. Our result that developmental stages do not critically affect callus and shoot formation in sorghum inflorescence culture is not in agreement with those reported by Brettell et al [14], who found that sorghum inflorescences less than 20mm in length produced more apparently embryo-like structures than the panicles over 20 mm in length.…”
Section: Response To In Vitro Culture Of Immature Inflorescences Frommentioning
confidence: 99%
“…Plant regeneration from inflorescence cultures has been reported in various cereal crops including wheat [2], rice [3], corn [4], barley [5], millet [6], rye [7], and triticale [8] and in several forage and turf grasses such as orchard grass [9], elephant grass [10], sudan grass [11], bermuda grass [12] and little blue stem [13]. The only report describing sorghum immature inflorescence culture was that of Brettell et al [14].…”
Section: Introductionmentioning
confidence: 99%
“…Plant regeneration has also been reported from calli initiated from different explants, namely, anthers [2][3][4], glumes [5], immature inflorescence [6], immature tassels [7][8][9], leaf segments [10][11][12], protoplasts [13], seedling segments [14][15][16], shoot tips [17][18][19], shoot apical meristem [20], mature embryos [15,21,22], and immature embryos [23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…More commonly, embryogenic calli or organs are the source of embryos or plantlets [2,7,9,13,18,22,23]. In addition, mesocotyls [8,21], seedling segments [19], tassel inflorescence segments [17], glumes [20], and shoot apices from ten-day-old seedlings (or at three-leaf stage) [1,10] have been the embryogenic or organogenic sources.…”
Section: Introductionmentioning
confidence: 99%